74.1k views
0 votes
Solve the system of equations using substitution. Show your work.

d + e = 6
d - e = 4

2 Answers

2 votes

Answer:

the solution is (1, 5)

Explanation:

If d - e = 4, then d = e + 4. Substitute e + 4 for d in the first equation:

d + e = 6 → e + 4 + e = 6. Then 2e = 2, and e = 1.

Subbing 1 for e in the second equation, we get d + e = 6, or d + 1 = 6.

Thus, d = 5, and the solution is (1, 5)

User James Meakin
by
5.8k points
3 votes

Answer:

d+e =6 d=5 and e=1

d-e=4

Explanation:

5+1=6

5-1=4

simple math you have to think hard to get it right might look easy but it is not

User Bbholzbb
by
6.0k points